Bounds on the density of sources of ultra-high energy cosmic rays from the Pierre Auger Observatory - Allekotte, Ingomar; Almela, Daniel Alejandro; Asorey, Hernán Gonzalo; Bertou, Xavier Pierre Louis; Dasso, Sergio Ricardo; de la Vega, Gonzalo Andrés; Dova, Maria Teresa; Etchegoyen, Alberto; Figueira, Juan Manuel; Filevich, Alberto; Gamarra, R. F.; Garcia, Beatriz Elena; et al. (IOP Publishing, 2013)
Fil: Allekotte, Ingomar. Comisión Nacional de Energía Atómica. Gerencia del Area Investigación y Aplicaciones No Nucleares. Gerencia de Física (Centro Atómico Bariloche). Grupo de Partículas y Campos; Argentina. Comisión Nacional de Energía Atómica. Centro Atómico Bariloche; Argentina. Comisión Nacional de Energía Atómica. Gerencia del Area de Energía Nuclear. Instituto Balseiro; Argentina